District heating pipes. Bonded twin pipe systems for directly buried hot water networks. Factory made fitting and valve assemblies of steel service pipes, polyurethane thermal insulation and one casing of polyethylene Part 2, (5th November 2019) - British Standards Institution,
No abstract available